Progressão referencial e sequências textuais argumentativas em artigos de opinião de FHC - Afonso, Adriana Eugênia Antony (2014)
This Master Degree Thesis is in the research line Text and Discourse, in written and oral modalities, and as a theme Referential Progression and Argumentative Textual sequences on texts of FHC. This research main objective is analyzing the referential progression and the argumentative textual sequences text of in Fernando Henrique Cardoso (FHC). The specifics objectives are to identify, describe and analyze the referential progression and argumentative sequences in texts of FHC; and interpret this relation between referential progression and argumentative sequences in texts of FHC. The theoretical basis is in the Textual Linguistic. To achieve our objectives, this research was based on the following authors: Bentes (2008), Fávero & Koch (2008) and Koch (2009), in the Textual Linguistic field; Koch & Marcuschi (1998), Mondada (2001), Koch (2008, 2009, 2010), Roncarati (2010) e Mondada & Dubois (2013), in the reference process field; Koch & Marcuschi (1998), Koch (2009, 2011a), Koch & Elias (2008, 2009), in referential progression field; and Adam (2008), in argumentative sequences field and textual planning. The obtained results in its analysis confirmed that the use of the nominal expressions as important strategy as a referential progression, which allows the interlocutor, recognizing by these textual choices, the communicative author´s purpose. The texts, indicates that the textual connections of statements, particularly from the argumentative textual, needs a large focus than the linguistic and structural